(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Gestational diabetes mellitus (GDM) has become more common and a cause of poor maternal and fetal outcomes for last few years. Literature has stated that GDM is related to elevated serum uric acid levels that can ultimately lead to unfavorable circumstances. The aim of the present study is to determine the frequency of hyperuricemia among patients with gestational diabetes. Objective: To determine the frequency of hyperuricemia among women with gestational diabetes. Study Design and settings: It was a cross-sectional study, conducted at the Department of Obstetrics and Gynecology, Liaquat University Hospital Hyderabad / Jamshoro. Duration: The duration of this study was seven months from 7th August 2023 to 7th February 2024. Material and Methods: The patients aged 16-45 years presenting with gestational diabetes were enrolled in the study. Informed consent was taken from the patient/caretaker after explaining the risks and benefits of the study. The outcome variable, i.e. hyperuricemia, was assessed. The collected data was entered and analyzed by using SPSS v. 17 and appropriate statistical tests were applied. Result: In this study, we enrolled 150 women presenting with gestational diabetes. The mean age of women was 27.25 ± 4.48 years. The mean duration of GDM was 8.25 ± 2.55 weeks, and the mean uric acid level was 6.57 ± 2.59. Moreover, the frequency of hyperuricemia among women with gestational diabetes was 70 (46.67%). Conclusion: This study highlights the high prevalence of hyperuricemia among women with gestational diabetes, emphasizing the need for monitoring uric acid levels, especially in women with associated risk factors.